The Importance of the Theory of Pragmatic Truth on the Development of Teacher Professionalism - Simanjuntak, Nensy Megawati; Padmasari, Arumtyas Puspitaning (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2024)
This research aims to explain the importance of mastering concepts and knowledge of the pragmatic theory of truth. Mastering the pragmatic theory of truth will lead educators to a more intelligent and conscientious pattern of self-development. Education involves two basic components, namely: educators and students. Educators who are the spearhead of the education system must have full self-awareness of their own development. One of the self-development that an educator needs to do is develop professionalism. Teacher professionalism can be developed in many ways, one of which is developing knowledge of concepts or theories that are relevant to their field of work. One of the concepts or theories that educators need to master and develop is the pragmatic theory of truth. This research is a descriptive phenomenological analysis research. The data sources used were 26 teachers at Xin Zhong Middle School in Surabaya. This research was conducted using interview and observation techniques as a way to obtain data. The research was conducted because it was found that there were several educators who did not understand the concept of pragmatic truth which was demonstrated through the attitudes and viewpoints of educators, thereby influencing the learning and professional processes that occurred in educational institutions. This research found that the pragmatic theory of truth which is well mastered by educators will produce individuals who are more intellectual and virtuous by involving conscience as an indicator in expanding knowledge. _________________________________________________________________________________________ Penelitian ini bertujuan untuk memaparkan pentingnya penguasaan konsep dan pengetahuan terhadap teori kebenaran pragmatis. Adanya penguasaan teori kebenaran pragmatis akan membawa pendidik ke pola pengembangan diri yang lebih berakal dan bernurani. Pendidikan melibatkan dua komponen dasar yakni: pendidik dan peserta didik. Pendidik yang merupakan ujung tombak terhadap sistem pendidikan harus memiliki kesadaran diri penuh terhadap pengembangan dirinya. Salah satu pengembangan diri yang perlu dilakukan oleh seorang pendidik adalah pengembangan profesionalisme. Profesionalisme guru dapat dikembangkan melalui banyak cara, salah satunya adanya pengembangan pengetahuan terhadap konsep atau teori yang relevan dengan bidang pekerjaanya. Salah satu konsep atau teori yang perlu dikuasai dan dikembangkan oleh pendidik adalah teori kebeneran pragmatis. Penelitian ini merupakan penelitian analisis deskriptif fenomenologi. Sumber data yang dijadikan adalah guru SMP Xin Zhong Surabaya yang berjumlah 26 orang. Penelitian ini dilakukan dengan menggunakan teknik wawancara dan observasi sebagai cara untuk memeroleh data. Penelitian dilakukan karena ditemukan adanya beberapa pendidik yang tidak memahami konsep kebenaran pragmatis yang ditunjukkan melalui sikap dan sudut pandang pendidik sehingga memengaruhi proses pembelajaran dan profesional yang terjadi di lembaga pendidikan. Penelitian ini menemukan bahwa teori kebenaran pragmatis yang dikuasai dengan baik oleh pendidik akan melahirkan pribadi yang lebih berintelektual dan berbudi pekerti dengan melibatkan nurani sebagai indikator dalam meluaskan pengetahuan.